2022
DOI: 10.22159/ijap.2022v14i5.44315
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of Astragalin-Loaded Polymeric Nanoparticles Using Central Composite Factorial Design

Abstract: Objective: The objective of the present study was to develop and optimize Astragalin-loaded polymeric nanoparticles (AST-NPs) using a central composite factorial design (CCD). Methods: AST-NPs were prepared by the dialysis method. CCD was employed to study the influence of formulation factors, polymer concentration, aqueous organic phase ratio, and process parameter stirring time on dependent physicochemical characteristics, particle size, zeta potential, and percentage entrapment efficiency (%EE) of the drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…1b and the curve in the contour plot fig. 1c also assure the same [38]. Hence, the drug entrapment efficiency will increase with an increase in all three factors [39].…”
Section: Effect Of Factors On Particle Size (R1)mentioning
confidence: 89%
See 1 more Smart Citation
“…1b and the curve in the contour plot fig. 1c also assure the same [38]. Hence, the drug entrapment efficiency will increase with an increase in all three factors [39].…”
Section: Effect Of Factors On Particle Size (R1)mentioning
confidence: 89%
“…The results are presented in table 6. The low magnitude of relative error, less than±2%, confers the robustness and predictability of software in preparing the stable Favipiravir-loaded PLGA nanoparticles [38,44]. This result indicated that there was no interaction between favipiravir and polymers during the preparation of favipiravirloaded PLGA nanoparticles [22,24].…”
Section: Numerical and Graphical Optimisationmentioning
confidence: 90%
“…Synthetic polymers are the most versatile materials, and their use in biomedical applications includes contact lenses, pharmaceutical vehicles, dental materials, substrates for tissue engineering, and others [43]. Research should focus on developing biodegradable and/or bioabsorbable synthetic polymers that can decompose as tissue regeneration progresses, as is the case with polyacrylates, polysiloxanes, polyamides, polycarbonates, polyesters, polyurethanes, polystyrenes, synthetic polypeptides, polyalkenes, and polyols [44,45].…”
Section: Synthetic Polymeric Biomaterialsmentioning
confidence: 99%
“…It has been endorsed in orthopedics as an adhesive for bones, cranial prostheses, and bone repairs [45,46]. Other PMMA applications also include its use as a vehicle for delivering genetic material, replacing viral vehicles [44].…”
Section: Polyacrylatesmentioning
confidence: 99%